Linkages between soybean and neotropical deforestation: Coupling and transient decoupling dynamics in a multi-decadal analysis - Gasparri, Nestor Ignacio (2013)
Soybean expansion, driven by growing global meat demand, has accompanied neotropical deforestation in past decades. A recent decoupling between soybean production and deforestation in Brazil is taken as evidence of efficient deforestation regulation. Here, we assessed the relationships between soybean economy, livestock production and deforestation from 1972 to 2011 in Northern Argentina Dry Chaco. We used Panel Analysis to evaluate the relationship between soybean cultivated and deforested area in different periods and we used high resolution time series analysis of a deforestation hotspot, to explore links between soybean economy, cattle ranching and deforestation. In northern Argentina, 2.7 millions ha were deforested from 1972 to 2011, 56% of which occurred after 2002. The results of the Panel analysis indicate a strong link between soybean expansion and deforestation but with variation among periods mediated by the links between soybean and livestock productions. Deforestation was strongly coupled with soybean expansion during the 1972?1997 and 2002?2011 periods; but was largely decoupled between 1997 and 2002, when strong increments in production were accompanied by low deforestation. The high resolution analysis also indicated contrasting levels of association after and before 1997. The soybean deforestation decoupled periods in Brazil and Argentina shared similarly weak economic incentives for soybean production, rapid technological innovation and preceding high deforestation periods. In the Argentine case, when economic incentives turned positive after a 5-years decoupled period, new government measures were unable to regulate deforestation. Our study suggests that macroeconomic factors can be a much stronger deforestation force compared with domestic legal frameworks. Effectiveness of neotropical deforestation regulation should be carefully monitored and interpreted with caution paying special attention to global economic context for soybean expansion.